Failure of the defendant to appear at the court as a ground for postponement of criminal proceedings: Problem aspects in practice - Senyk, Taras (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
The non-arrival of the defense attorney during the trial is one of the main grounds for postponement of the trial in criminal proceedings. The analysis of judicial practice made it possible to conclude that the absence of a defense attorney at a court hearing, if participation is mandatory, is also a fairly common reason for annulment of decisions and sentences of the court of first instance with the appointment of a new trial in connection with the violation of the requirements of the criminal procedural law. At the same time, it is known that the non-appearance of a party to a criminal proceeding does not prevent the proceedings only if the person was properly notified of the date, time and place of the trial and did not provide valid reasons for his non-appearance.In view of this, the question of classifying the reasons for the defense attorney’s non-appearance as legitimate remains a difficult one. Criminal procedural legislation leaves the resolution of the specified issue entirely to the discretion of the court. The exception is Art. 138 of the Criminal Procedure Code of Ukraine, which establishes a list of valid reasons for a person’s non-arrival at a summons, but this list is not exhaustive. In addition, the Bar Council of Ukraine adopted a decision regarding the validity of the reasons for the absence of lawyers to participate in court hearings during the consideration of cases, investigative actions and other jurisdictional procedures under martial law. Therefore, it is important for an in-depth study of the non-appearance of a defense attorney at a court session to conduct an analysis of court practice in Ukraine.